The role of biodiversity for ecosystem functions in polar sea-ice ecosystems - Ehrlich, Julia (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2021)
In the Arctic Ocean, changes caused by global climate warming have been the focus of research for about two decades. Especially the decline and loss of sea ice, but also the increasing inflow of Atlantic Water into the Arctic Ocean or the northward shift of sea-ice formation, are studied processes related to climate change. Those physical changes will undoubtedly affect the Arctic marine ecosystem. Our knowledge of this unique ecosystem, though, is still incomplete, which makes it difficult to assess the consequences of ongoing climate change. More recently, the research focus has been on the importance of ice algae and phytoplankton for the Arctic marine food web. As the main primary producers, they constitute an important food source for many ice-associated (sympagic) species that rely on the ice-algal bloom in spring and the phytoplankton bloom in summer. Sympagic species are important transmitters of carbon from the sea-ice to pelagic and benthic communities. In order to assess the consequences of environmental changes for sympagic communities, we need to broaden our basic understanding of underlying ecosystem functions, such as biomass or carbon cycling. Following this goal, we used a unique approach to measure physical parameters and sample sympagic organisms of the sea-ice and under-ice environment in the Eurasian Basin. We combined sea-ice coring and trawling with the Surface and Under-ice Trawl. The latter is equipped with an array of sensors to measure environmental parameters, e.g., sea-ice thickness, water temperature, salinity, and chlorophyll a concentration, whilst collecting fauna. The overarching aim of this study is to further our understanding of the Arctic sympagic ecosystem regarding its biodiversity and related ecosystem functions in the Eurasian Basin. Specific objectives are to 1) generate a quantitative inventory of the biodiversity, community structure, and abundance of sea-ice meiofauna and under-ice fauna, 2) characterize physical habitat properties over large scales to identify ...